Natural fillers as reinforcement for closed-molded polyurethane foam plaques: Mechanical, morphological, and thermal properties. (June 2021) - Husainie, Syed Muhammad; Deng, Xiaohan; Ghalia, Mustafa Abu; Robinson, Jason; Naguib, Hani E.
Highlights: Natural fillers are used for the reinforcement of closed-molded polyurethane foams. Cellulose, chitin, hazelnut, and eggshell are embedded with uniform dispersion. The properties are studied based on mechanical, thermal, and morphological analysis. The composite foams show improvements in the tensile and resiliency properties. Abstract: Natural fillers including cellulose, chitin, hazelnut, and eggshell are some of the most abundant bio-resources available for performance-cost-benefit applications. For this study, the aforementioned fibers were added to pure polyurethane foam and the properties were investigated based on mechanical (tensile, split tear, elongation, resilience, compression set, and hardness), thermal (thermogravimetric and differential scanning calorimetry), and morphological analyses. These natural fibers were added in wt. % of 1 %, 2.5 %, and 5 % using high shear mixing rates. The closed molded polyurethane foam was prepared using an addition reaction of polyol and isocyanate. The resulting foam composites embedded with natural fibers had uniform color distribution, indicating good fiber dispersion. 1 % fiber loading showed improvements in tensile and resiliency, whereas split tear properties decreased. Moreover, morphological results indicated uniform foaming and dispersion of fillers. This study reinforces the possibility of a more sustainable future by replacing synthetic fillers with natural fillers in industrial applications, including in the automotive, textile, construction, and other leading consumer-based industries.